Religiusitas dan Toxic Friendship di Kalangan Peserta Didik - Azmi, Ulil; Yaqin, Ainul; Saifuddin, Saifuddin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
In modern times like this, teenagers are faced with pressure and influence from various sources, such as social media, western culture, and the surrounding environment. Religiosity has an important role, because religiosity can be a source of support, moral guidance and spiritual strength in facing life's challenges. Teenagers' level of religiosity will influence their behavior. If teenagers' level of religiosity is high, they will tend to show behavior that reflects religious life. On the other hand, teenagers with a low level of religiosity will show behavior that is less related to religious aspects. By understanding the field of religion, students are able to differentiate between friendship relationships that support individual growth and those that can hinder individual development. This arises because it can avoid detrimental friendships or what is usually called toxic friendship. The aim of this research is to analyze the influence of religiosity on toxic friendship in students at Wachid Hasyim 10 Prambon Middle School. The research method used is quantitative with simple linear regression analysis. The data collection technique was through a questionnaire filled out by 200 respondents. The results of data analysis using SPSS show that the level of students' religiosity is in the high category with an average value of 178.35. Meanwhile, the level of toxic friendship is in the low category with an average value of 38.98. The normality test shows that the data is normally distributed with a sig value of 0.896 which is greater than 0.05. Based on the results of inferential analysis, there is a significant negative influence between religiosity and toxic friendship with a significance value of 0.000 which is smaller than 0.05, and tcount of -5.900 which is greater than ttable of 1.653. Religiosity influences toxic friendship by 15%, while 85% is influenced by other factors. This research concludes that the higher the level of religiosity of students, the lower the level of toxic friendship they experience. These results emphasize the importance of strengthening religious values ​​in an effort to reduce toxic friendships among students.